2009
DOI: 10.1007/s12540-009-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca addition on microstructure of twin-roll cast AZ31 Mg alloy

Abstract: A twin-roll cast (TRC) AZ31-0.7Ca alloy sheet has been subjected to thermo-mechanical treatment (TMT) followed by annealing and its microstructure was evaluated. The as-cast microstructure of TRC AZ31-0.7Ca alloy is essentially similar to that of TRC AZ31 alloy, except for the presence of Al 2 Ca dispersoid particles. The presence of Al 2 Ca particles imparts significant changes to the microstructure of TMT-ed TRC alloy such as the refinement of grain size and evolution of textures different from those of ingo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…It should be noted that the stress-strain curve of the compression specimen showed curvature change at the early stage of deformation (strain < 0.2), a trend that is clearly different from that of the torsion test. As reported in previous works [18,19], the curvature change originates from the occurrence of tensile twinning during the compression test. Moreover, the present study Table 1.…”
Section: Flow Curves Of Compression and Torsion Testssupporting
confidence: 72%
“…It should be noted that the stress-strain curve of the compression specimen showed curvature change at the early stage of deformation (strain < 0.2), a trend that is clearly different from that of the torsion test. As reported in previous works [18,19], the curvature change originates from the occurrence of tensile twinning during the compression test. Moreover, the present study Table 1.…”
Section: Flow Curves Of Compression and Torsion Testssupporting
confidence: 72%
“…As the demand for reducing CO 2 emissions and increasing the fuel efficiency grows, magnesium alloys have received an increasing amount of attention as structural materials due to their excellent properties, such as their high specific strength, low density and stiffness [1][2][3]. Since the c/a ratio of the hexagonal close-packed (hcp) magnesium lattice is less than √ 3, extruded magnesium alloys, which have a strong basal texture, show large yield asymmetries between tension and compression due to the twinning effects during compression along the prior extruded direction [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] To this end, active research attempts have been made recently and successful results have been reported for valve metals by a utilizing microarc discharge oxidation (MDO) technique where dielectric breakdown were readily promoted on the anode by plasma-assisted high energy. [5][6][7] Depending on the substrates, metal oxide films with thin thicknesses were generated during the MDO coating so as to enhance corrosion and wear resistances.…”
Section: Introductionmentioning
confidence: 99%